PENENTUAN POTENSI LAHAN PERTANIAN PANGAN BERKELANJUTAN (LP2B) DAN LAHAN CADANGAN PERTANIAN PANGAN BERKELANJUTAN (LCP2B) DI KABUPATEN TANAH DATAR - rido koja; Ratna Wilis (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
This research was conducted in Tanah Datar Regency which aims to determine Sustainable Food Agricultural Land (LP2B) and Sustainable Food Agricultural Reserves (LCP2B) in Tanah Datar Regency. The method used is a descriptive approach with quantitative research and the data used is secondary data with data processing using the Boolean logic method. The results of this study indicate Sustainable Food Agricultural Reserves (LCP2B) has the potential for an area of ​​29,318.58 hectares or 21.16% of the total area of ​​the Regency. Lintau Buo District has the widest Sustainable Food Agricultural Reserves (LCP2B) potential, namely 4,765.67 hectares and Pariangan District is the smallest sub-district which is 552.32 hectares. Sustainable Food Agricultural Land (LP2B) covers an area of ​​27,754.64 hectares or 20.03% of the total area of ​​Tanah Datar Regency which is spread across all districts. Sungai Tarab District has the widest potential for Sustainable Food Agricultural Land (LP2B), namely 2,794.98 hectares and Batipuh Selatan District is the smallest sub-district, which is 759.93 hectares.